2017
DOI: 10.1007/s12298-016-0408-5
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity, population structure and association analysis in linseed (Linum usitatissimum L.)

Abstract: The present investigation aimed to explore the level of genetic diversity, determine the population structure in a larger set of germplasm of linseed using microsatellite marker and identify linked markers through association mapping. A total of 168 accessions of linseed were evaluated for major agro-economic traits and SSRs markers deployed for diversity assessment. A total of 337 alleles were amplified by 50 SSRs ranging from 2 to 13 with an average of 6.74 ± 2.8 alleles per loci. The neighbor joining based … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 41 publications
(44 reference statements)
3
16
0
Order By: Relevance
“…In our study, based on the identi ed SNP markers, the different sub-populations exhibited moderate diversity (average H = 0.22), which is in line with our expectation as ax possesses an autogamous reproduction system. A similar level of diversity was found in one study (42), though other studies revealed both low (43,44) and high (45,46) level of diversity of different group of ax germplasm. The variation in results may be due to the utilization of different markers and different genotype sets by the researchers.…”
Section: Discussionsupporting
confidence: 85%
“…In our study, based on the identi ed SNP markers, the different sub-populations exhibited moderate diversity (average H = 0.22), which is in line with our expectation as ax possesses an autogamous reproduction system. A similar level of diversity was found in one study (42), though other studies revealed both low (43,44) and high (45,46) level of diversity of different group of ax germplasm. The variation in results may be due to the utilization of different markers and different genotype sets by the researchers.…”
Section: Discussionsupporting
confidence: 85%
“…When the main factors accounting for population subdivision correlate with a trait under study (i.e., geographic distribution and flowering time), then marker–trait associations will undergo a more accentuated inflation of observed p -values as effect of the structure confounding factor [ 39 ]. In flaxseed, population structure has been assessed in varying numbers of accessions, where geographic origin and flax morphotype seemed to have been the main factors underlying population subdivisions [ 40 , 41 , 42 ]. In our association panel, the “red” and “blue” clusters were slightly differentiated ( F ST = 0.08), with a weak morphotypic effect on dendrogram topology, possibly due to the small number of fiber types ( n = 33) compared to the larger number of oilseed type accessions ( n = 153).…”
Section: Discussionmentioning
confidence: 99%
“…Molecular markers such as RAPD, AFLP, ISSR, SSR, IRAP, and SNP have been widely used in flax to measure the genetic diversity and population structure in different breeding programs (Soto-Cerda et al, 2012;Xie et al, 2018b), which provided the evinces to support the associations between geographic origin and morphological differences during flax seed spreading over the world (Smykal et al, 2011;Soto-Cerda et al, 2013;Chandrawati et al, 2017;Xie et al, 2018b). In the present study, cultivated flax was divided into oil flax, oil-fiber dual purpose (OF) and fiber flax groups.…”
Section: Oil Flax Population Is the Ancestor Of Cultivated Flaxmentioning
confidence: 99%